Decreased Information Replacement of Working Memory After Sleep Deprivation: Evidence From an Event-Related Potential Study - Zhang, Liwei; Shao, Yongcong; Liu, Zhongqi; Li, Chenming; Chen, Yuhong; Zhou, Qianxiang (Frontiers in Neuroscience, 2019)
Working memory components are altered after total sleep deprivation, both with respect to information replacement and result judgement. However, the electrophysiological mechanisms of working memory alterations following sleep restriction remain largely unknown. To identify such mechanisms, event-related potentials were recorded during the n-back working memory task, before and after 36 hours sleep deprivation. Thirty-one young volunteers participated in this study and performed a two-back working memory task with simultaneous electroencephalography (EEG) recording before and after total sleep deprivation and after 8 h time in bed for recovery (TIBR). Repeated measures analysis of variance revealed that, compared to resting wakefulness, sleep deprivation induced a decrease in the P200 amplitude and induced longer reaction times. ERP-component scalp topographies results indicated that such decrease primarily occurred in the frontal cortex. The N200 and P300 amplitudes also decreased after total sleep deprivation. Our results suggest that decreased information replacement of working memory occurs after 36 h of total sleep deprivation and that 8 h TIBR after a long period of total sleep deprivation leads to partial restoration of working memory functions. The present findings represent the EEG profile of working memory during mental fatigue.